Development of Augmented Reality-Based Digital Learning Media on Plant and Animal Cell Topics to Enhance the Analytical Skills of Eighth Grade Junior High School Students - Muchamad Rangga Hidayatulloh; Yayuk Mulyati; Yonna Divanka Yuanvanelli (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: Technological advances inside the industrial revolution 4.0 era have encouraged the educational world to offer interactive and contextual learning, mainly in growing better-order wondering abilities inclusive of analysis. The topic of plant and animal cells in science lessons is abstract and often difficult for students to grasp when taught conventionally.Aims: The aim of this study was to develop using plant and animal cell material to enhance the analytical skills of eighth-grade junior high school students.Methods: The stages of media development encompass analysis, design, development, implementation, and assessment. The media was created using Unity and Vuforia software with marker-based tracking techniques and validated by media and subject matter experts.Results: Validation by material specialists and media specialists confirmed validity levels of 96.59% and 96.25%, respectively. Readability (98.12%) and practicality (95%) tests also showed excellent scores.Conclusion: With these results from this study, it could be concluded that the AR-based learning media developed is appropriate for use in science learning because it can present abstract material more interactively and efficaciously in schooling students' analytical talents.